ANALISIS MOTIVASI TERORIS PEREMPUAN INDONESIA DILIHAT DARI PERSPEKTIF TEORI IDENTIFIKASI DIFERENSIAL - Hutabarat, Alfira Yulisza (Sekolah Tinggi Ilmu Kepolisian, 2023)
Terrorism is a crime that often attracts public attention. There are various reasons that underlie the terrorists carry out their actions. The perpetrators of terrorism are usually dominated by men. In this paper, we will discuss women terrorists in Indonesia, especially regarding the motivations underlying their actions. The Differential Identification Theory put forward by Daniel Glaser will be used in this study to analyze the motivations of female terrorists. A qualitative approach is used in research by collecting data through secondary data studies. Secondary data was obtained from various previous studies and research documents of the involvement of women in acts of terrorism in six Polda areas conducted by CTRS-PTIK. This research shows that acts of terror committed by women and women's involvement in terrorism are based on a sense of devotion to the family, whose domination comes from men or commonly known as patriarchal culture and is motivated by religious fanaticism which leads to self-identification with groups that claim to be the truest Muslims. Female terrorists are constructed by their social environment and what they identify as part of themselves.Â